An Undoped Tri‐Phase Coexistent Cathode Material for Sodium‐Ion Batteries. (5th August 2022) - Li, Ranran; Gao, Jian; Li, Junpeng; Huang, Hao; Li, Xiaolei; Wang, Wenlong; Zheng, Li‐Rong; Hao, Shu‐Meng; Qiu, Jieshan; Zhou, Weidong
Abstract: The layered transition‐metal‐oxide materials are one type of promising cathode materials for sodium‐ion batteries, which typically include P2, P3, and O3 phases, and each has its own advantages and challenges. Taking into account the complementarity of each single‐phase structure, constructing the composite structures is an efficient pathway to stabilize the structure and improve the electrochemical performance. Herein, three composite cathode materials owning the phase structures of P3/P2, P2/O3, and P3/P2/O3 are prepared by changing the calcinating conditions without introducing any doping element. Among them, the composite of P3/P2/O3 shows the best capacity retention of 80 mAh g –1 after 200 cycles and the highest rate performance of 100 mAh g –1 at a current density of 750 mA g –1 . The improved electrochemical performance can be attributed to the staggered arrangement of different phase structures and the gradient Na‐extraction/intercalation voltages of different phases. The slip of the transition metal layer is subjected to the constraint of the adjacent phase structure, thus inhibiting the phase transformation for capacity fading. This work provides an easy way for the preparation of composite cathode structures and brings a clear case for understanding the advantage of composite structures on electrochemical performance. Abstract : Undoped bi‐phase and tri‐phase cathode materials for sodium‐ion batteries are prepared to investigate the exclusive contributions of the multi‐phase structure on electrochemical performance, in which, the tri‐phase cathode show better performance than the bi‐phase cathode and then single‐phase cathode, owing to a structural constraint effect during Na + ‐extraction/intercalation and the resulting restricted phase transformations.